Teeth - Moskowitz, Hannah (Simon Pulse, 2013)
"Rudy's life is flipped upside-down when his family moves to a remote, magical island in a last attempt to save his sick younger brother, Dylan. While Dylan recovers, Rudy sinks deeper and deeper into his loneliness"--